HUBUNGAN AKTIVITAS FISIK DENGAN PHLEBECTASIA PASCA ARTERIOVENOUS SHUNT PASIEN HEMODIALISIS DI RS PKU MUHAMMADIYAH YOGYAKARTA UNIT II - Arnis Khaerunisa (FKU 15 UMY 559, 2015)
*559 Hemodialysis is therapy to replace the kidney function. Hemodialysis which indicated a routine and long term require a vascular access. Arteriovenous shunt (AVS) is the most common vascular access used in Indonesia. The often case after the installation of AVS is the phlebectasia. The purpose of this study was to examine the relationship between physical activity with the emergence of phlebectasia in hemodialysis patient. This research used analytic observational, design cross sectional to 96 hemodialysis patients in hemodialysis unit PKU Muhammadiyah Yogyakarta Unit II Hospital since may 2015 until june 2015. The data were collected using IPAQ (International Physical Activity Questionaire) questionaire through interview to the patients. The finding of this study using chi square result 23 subject has phlebectasia with high physical activity (24,0%), 24 subjects have phlebectasia with low physical activity (25,0%), 13 subjects have not phlebectasia with high physical activity (13,5%) and 36 subjecst have not phlebectasia with low physical activity (37,5%). In conclusion, there is a significant relationship between physical activity with phlebectasia where p=0,023 event the correlation is weak r=0,231. Keyword : Hemodialysis, Phlebectasia, Venectasia, Arteriovenous Shunt, Physical Activity